Numerical Study of a 3D Two-Phase PEM Fuel Cell Model via a Novel Automated Finite Element/Finite Volume Program Generator (Communications in Computational Physics, 2012)
Numerical methods of a 3D multiphysics, two-phase transport model ofproton exchange membrane fuel cell (PEMFC) is studied in this paper. Due to thecoexistence of multiphase regions, the standard finite element/finite volume methodmay fail to obtain a convergent nonlinear iteration for a two-phase transport modelof PEMFC [49, 50]. By introducing Kirchhoff transformation technique and a combined finite element-upwind finite volume approach, we efficiently achieve a fast convergence and reasonable solutions for this multiphase, multiphysics PEMFC model.Numerical implementation is done by using a novel automated finite element/finitevolume program generator (FEPG). By virtue of a high-level algorithm description language (script), component programming and human intelligence technologies, FEPGcan quickly generate finite element/finite volume source code for PEMFC simulation.Thus, one can focus on the efficient algorithm research without being distracted bythe tedious computer programming on finite element/finite volume methods. Numerical success confirms that FEPG is an efficient tool for both algorithm research andsoftware development of a 3D, multiphysics PEMFC model with multicomponent andmultiphase mechanism.